Pengaruh Layanan Informasi Melalui Metode Reward and Punishment Terhadap Motivasi Belajar Siswa Selama Pembelajaran Online Kelas VII di SMP RK Deli Murni Deli Tua - Nazariah Nazariah; Ika Sandra Dewi (Medan State University, 2023)
Learning motivation is anything that can motivate students or individuals to learn. Without learning motivation, a learner will not learn and ultimately will not achieve success in learning. Therefore researchers use information services through the reward and punishment method in order to increase student motivation during online learning. The population in this study were all class VII students of SMP RK Deli Murni Deli Tua a total of 131 students. Then the determination of the sample was carried out by purposive sampling, namely as many as 30 students. Data collection was carried out by distributing questionnaires pre-test before treatment and post-test after treatment. The method used in this research is quasi-experimental. Based on the data management carried out, the average pre-test value = 71.3 with a standard deviation of 71.46 with details of the medium category of 1 person or 3.33%, the low category is 29 people or 96.67% while the average post-test value = 94.63 with a standard deviation of 94.95 with details of the high category of 2 people or 6.67%, the medium category is 28 people or 93.33%. It is proved by testing the hypothesis of the research that the t test value is 5.04 and t table 5% level is 2.045 (t count 5.04 > t table 2.045). Based on the data analysis, it can be concluded that there has been a change in students' learning motivation during online learning for class VII at SMP RK Deli Murni Deli Tua.